A comparative study of CE‐SDS, SDS‐PAGE, and Simple Western: Influences of sample preparation on molecular weight determination of proteins. Issue 3 (30th November 2020) - Wiesner, Rebecca; Scheller, Christin; Krebs, Finja; Wätzig, Hermann; Oltmann‐Norden, Imke
Abstract: The development of capillary electrophoresis, especially CE‐SDS devices, has led CE‐SDS to become an established tool in a wide range of applications in the analysis of biopharmaceuticals and is increasingly replacing its method of origin, SDS‐PAGE. The goal of this study was to evaluate the comparability of molecular weight (MW) determination especially by CE‐SDS and SDS‐PAGE. For ensuring comparability, model proteins that have little or no posttranslational modifications and an IgG antibody were used. Only a minor influence of sample preparation conditions, including sample buffer, temperature conditions, and different reducing agents on the MW determination were found. In contrast, the selection of the MW marker plays a decisive role in determining the accurate apparent MW of a protein. When using different MW markers, the deviation in MW determination can exceed 10%. Interestingly, CE‐SDS and 10% SDS‐PAGE hardly differ in their trueness of MW determination. The trueness in relation to the reference MW for each protein was calculated. Although the trueness values for the model proteins considered range between 1.00 and 1.11 using CE‐SDS, they range between 0.93 and 1.03 on SDS‐PAGE, depending on the experimental conditions chosen.